THE BENEFITS OF ZAKAT IN MITIGATING FINANCIAL DISTRESS: EVIDENCE FROM INDONESIAN SHARIAH BANKS - Farida; Raharja, Bayu Sindhu (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2023)
The primary objective of this study is to examine the relationship between zakat and financial distress within the context of Islamic banking. The research methodology employed in this study involves employing linear regression analysis based on data extracted from the annual reports of Islamic banks in Indonesia spanning the years 2015 to 2019. The findings indicate that zakat constitutes a significant variable capable of mitigating the financial distress experienced by Islamic banking institutions in Indonesia. The findings of this study offer valuable practical and empirical insights. On the empirical front, this research provides evidence that supports the reliability and effectiveness of the Springate Model in predicting financial distress. By demonstrating the model's robustness, this study contributes to the empirical literature in the field. On the practical side, the study offers practical considerations and implications for bankers and financial professionals. Specifically, it highlights the significance of monitoring and analyzing key financial ratios as a proactive measure to anticipate and address potential financial threats within their respective firms. These practical insights can inform decision-making processes and help banking professionals take appropriate actions to safeguard their institutions against financial distress.